Information systems and organizational memory: a literature review - Barros, Victor Freitas Azeredo (2015)
The advancement of technologies and Information Systems (IS) associated with the search for success in the competitive market leads organizations to seek strategies that assist in acquisition, retention, storage, and dissemination of knowledge in the organization in order to be reused in time, preserving its Organizational Memory (OM). The Organizational Memory Information Systems (OMIS) rises as an enhancer of the OM, providing effective support and resources for the organization, assisting on decision-making, in the solution of problems, as well as in quality and generation of products and services. This article is an analysis of some OMIS selected from a literature review about its features and functionality in order to understand how these information systems are seen by the organizations. With this research, we realized that it is still inexpressive this relationship between OM and IS, even with the existence of some cases of success in the use of OMIS in the literature. The literature reveals that the individuals' knowledge is not integrated on information systems management process in most organizations, getting much of the knowledge of individuals generated in the organization retained in own individual. It is easy to see that there is a need for strategies and mechanisms in the organization to stimulate and provide a better knowledge sharing between individuals which, when associated to IS, allow greater control and effective use of the Organizational Memory.